Polyphenol-Based Therapeutic Strategies for Mitochondrial Dysfunction in Aging - Tamara Maksimović; Carmen Gădău; Gabriela Antal; Mihaela Čoban; Oana Eșanu; Elisabeta Atyim; Alexandra Mioc; Codruța Șoica (Biomolecules, 2025)
Aging, a progressive and time-dependent decline in physiological functions, is driven by interconnected hallmarks, among which mitochondrial dysfunction plays a central role. Mitochondria not only regulate energy production but also play key roles in other cellular processes, including ROS generation, apoptosis, and metabolic signaling—all of which decline with aging. Polyphenols are a diverse group of natural compounds found in fruits, vegetables, tea, and wine; they emerged as promising anti-aging agents due to their ability to modulate several hallmarks of aging, particularly mitochondrial dysfunction. This review explores how various polyphenolic classes influence mitochondrial function and mitigate aging-related decline. These natural compounds have been shown to reduce oxidative stress, increase energy production, and help maintain normal mitochondrial structure. Moreover, in vitro and in vivo studies suggest that polyphenols can delay signs of aging and improve physical and cognitive functions. Overall, polyphenols show great potential to promote healthy aging and even delay the decline in physiological functions by protecting and enhancing mitochondrial health.